'Pseudo‐Dominant' Inheritance in Friedreich's Ataxia: Clinical and Genetic Study of a Brazilian Family. Issue 4 (30th September 2014) - Moro, Adriana; Martinez, Alberto R.M.; Karuta, Simone C.V.; Munhoz, Renato P.; Moscovich, Mariana; Germiniani, Francisco M.B.; Arruda, Walter O.; Raskin, Salmo; Teive, Hélio A.G.
Abstract Friedreich's ataxia (FA) is an autosomal recessive inherited disorder characterized by progressive gait and limb ataxia, hypertrophic cardiomyopathy, limb muscular weakness, and areflexia with positive extensor plantar response. Loss of vibratory and position sense, skeletal abnormalities, and dysarthria are common comorbid features. The wide spectrum of disease may lead to a diagnostic challenge, and in such a scenario, the inheritance pattern might be a clue to diagnosis. A rare and peculiar pattern observed in some families is the pseudodominant pattern that is usually characterized by phenotypic variation, which, in turn, could make it even harder to get to a correct diagnosis. This pattern, although seemingly similar to a true dominant pattern of inheritance, should be kept in mind whenever one is evaluating a family with FA. We evaluated a Brazilian family of Italian ancestry with variation of phenotype among affected siblings.